A large swelling of the tongue. (6th December 2011) - Ray, Jay Gopal; Bhattacharya, Sourav; Mahato, Basudev; Mukherjee, Sanjit; Chaudhuri, Keya
Abstract : Hyalinising clear cell carcinoma (HCCC) is an infrequent distinct histological subtype of clear cell adenocarcinoma encountered in minor salivary glands which can be confused with a variety of clear cell-rich tumours. The entity of HCCC should be considered in patients presenting with well-circumscribed longstanding nodular enlargement without any other significant abnormality. HCCC is often difficult to diagnose due to its unusual presentation. This report presents a male patient who reported with a complaint of 2 month history of a large swelling on the tongue. The clinical, radiological, histological and immunohistochemical findings, confirmed the diagnosis of HCCC.